2020
DOI: 10.32332/pedagogy.v8i2.2274
|View full text |Cite
|
Sign up to set email alerts
|

Jigsaw Strategy for Cooperative Learning in an English Reading Class: Teacher’s and Students’ Beliefs

Abstract: The study investigated teacher’s and students’ beliefs on jigsaw learning activities for cooperative learning. It was conducted to fill the void in the literature on jigsaw in the second language (L2) instruction seen from teachers’ and students’ beliefs. Twenty-four students of the English Language Education Department taking Intensive Reading class and the class teacher were involved in this study, employing observation and semi-structured interviews, the data of which were analyzed using Thematic Analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Our teacher participant's grouping practice, i.e., not putting her students in mixed groups, might not align with the underlying tenet of Jigsaw as proposed by Aronson (2021) and recommendations from the existing studies (Olukayode et al, 2014), especially for nurturing students' ability for empathy and compassion (Aronson, 2002). Nevertheless, her practice suited her teaching contexts and was approved by her students, which addressed accountability issues such as students displaying effortless actions during Jigsaw processes as raised by Susanti and Subekti (2020). Our teacher participant's practice of dedicating more time to students she deemed having a low level of reading comprehension ability demonstrated her effort to reap the benefits of Jigsaw, i.e., everyone has a contribution and does not feel inferior in delivering their opinions and ideas (Dhull & Verma, 2019).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our teacher participant's grouping practice, i.e., not putting her students in mixed groups, might not align with the underlying tenet of Jigsaw as proposed by Aronson (2021) and recommendations from the existing studies (Olukayode et al, 2014), especially for nurturing students' ability for empathy and compassion (Aronson, 2002). Nevertheless, her practice suited her teaching contexts and was approved by her students, which addressed accountability issues such as students displaying effortless actions during Jigsaw processes as raised by Susanti and Subekti (2020). Our teacher participant's practice of dedicating more time to students she deemed having a low level of reading comprehension ability demonstrated her effort to reap the benefits of Jigsaw, i.e., everyone has a contribution and does not feel inferior in delivering their opinions and ideas (Dhull & Verma, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…However, our probe into the literature also reveals challenges in its use. Susanti and Subekti's (2020) study showed that not all students gave their best effort and tended not to contribute to the discussion, although the Jigsaw process seemed practical. Similarly, students' achievement did not show significant results, although their enthusiasm and motivation increased when learning in a Jigsaw setting (Sabbah, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…In this technique, students work with the same group members but with different backgrounds. Moreover, the jigsaw cooperative learning model focuses on teamwork or small groups that provide information to each other in the team or group (Mengduo & Xiaoling, Orprayoon, 2014;2010;Susanti & Subekti, 2020).…”
Section: Introductionmentioning
confidence: 99%